HLA-B51 Carriers are Susceptible to Ocular Symptoms of Behçet Disease and the Association between the Two Becomes Stronger towards the East along the Silk Road: A Literature Survey. (2nd January 2017) - Horie, Yukihiro; Meguro, Akira; Ohta, Tohru; Lee, Eun Bong; Namba, Kenichi; Mizuuchi, Kazuomi; Iwata, Daiju; Mizuki, Nobuhisa; Ota, Masao; Inoko, Hidetoshi; Ishida, Susumu; Ohno, Shigeaki; et al.
ABSTRACT: Purpose : Behçet disease (BD) is predominantly found between East Asia and the Mediterranean basin along the historic Silk Road. HLA-B51 is known to be strongly associated with BD. We investigated the association between HLA-B51 and the ocular manifestations of BD among various ethnic groups. Methods : A literature survey was conducted, and 18 articles written in English were reviewed. Results : A strong correlation was found between HLA-B51 and ocular lesions in the entire cohort discussed in the reviewed articles (OR = 1.76, p = 0.000057). HLA-B51 was shown to have a strong association with ocular manifestations of BD patients in East-Eurasian (OR = 2.40, p = 0.0030) and Middle-Eurasian (OR = 1.87, p = 0.0045), but not in West-Eurasian (OR = 1.28, p = 0.35) areas. This correlation seemed to become stronger towards the east. Conclusions : A meta-analysis showed that the correlation became stronger towards the east along the Silk Road. The study results may facilitate understanding of the etiology and characteristics of BD.